1997
DOI: 10.1002/(sici)1097-4628(19970207)63:6<787::aid-app11>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Microwave polymerization of poly(methyl acrylate): Conversion studies at variable power

Abstract: Methyl acrylate (MA) was polymerized by microwave radiation at three different powers, namely, 200, 300, and 500 W. The percentage conversion of the reaction was followed by Fourier transform infrared (FTIR) spectroscopy. The specimen temperature during the polymerization process was measured to select a suitable temperature for comparison with the conventional method. The results indicate that a similar comparable temperature of about 52ЊC was found for all the microwave power settings tested. The microwave p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 6 publications
2
34
0
2
Order By: Relevance
“…Because of the quick and instantaneous heating, the polymerization of monomers could be damaged by the microwave energy. However, classical studies have been shown that microwavepolymerized acrylic resin presents lower or the same residual monomer levels relative to conventionally polymerized resins (McCabe & Basker, 1976;Austin & Basker, 1980;Austin & Basker, 1982;Huggett et al, 1984;DeClerck, 1987;Truong & Thomasz, 1988;Al Doori et al, 1988;Sadamori et al, 1994;lbay et al, 1994;Yunus et al, 1994;Shlosberg et al, 1989;Jacob et al, 1997). Other researches showed resin polymerized by microwave energy presented similar solubily, residual monomer or water sorption levels than conventional or fast polymerization process.…”
Section: Solubility Residual Monomer and Water Sorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the quick and instantaneous heating, the polymerization of monomers could be damaged by the microwave energy. However, classical studies have been shown that microwavepolymerized acrylic resin presents lower or the same residual monomer levels relative to conventionally polymerized resins (McCabe & Basker, 1976;Austin & Basker, 1980;Austin & Basker, 1982;Huggett et al, 1984;DeClerck, 1987;Truong & Thomasz, 1988;Al Doori et al, 1988;Sadamori et al, 1994;lbay et al, 1994;Yunus et al, 1994;Shlosberg et al, 1989;Jacob et al, 1997). Other researches showed resin polymerized by microwave energy presented similar solubily, residual monomer or water sorption levels than conventional or fast polymerization process.…”
Section: Solubility Residual Monomer and Water Sorptionmentioning
confidence: 99%
“…Both characteristics of the polymerization rate and conversion, are proportional to the concentration of the reactive species as well as to the instantaneous temperature (Urabe et al, 1999). For the microwave-cured acrylic resins, it has been demonstrated that the temperature developed during the reaction is not constant: it increases quickly at the beginning, goes through a maximum and then decays, being able to reach peaks of the order of 150-200 ºC, depending on the working conditions (Gourdinne et al, 1979;Jacob et al, 1997). Hence, both the power of the microwave and the time of exposition can be regulated to control in these www.intechopen.com systems the rate of polymerization and the conversion degree.…”
Section: Porosity and Color Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Primedeno je da se proizvod dobija delimično kao porozan, a delimično kao kompaktan, pri čemu deo koji je kompaktan pokazuje svojstva slična standardno dobijenom PMMA *30]. Ispitivanje stepena konverzije MMA pri termičkoj i polimerizaciji u mikrotalasnom polju, pokazalo je da se u opsegu temperature od 70 °C do 90 °C dostiže granična konverzija MMA od 90%, pri termičkoj polimerizaciji, dok se pri istim uslovima u mikrotalasnom polju konverzija krede od 78% do 88%, uz smanjenje snage sa 500 W na 200 W [31]. I drugi izvori pominju da se mikrotalasnom polimerizacijom metilmetakrilata i itakonata dobijaju manje molarne mase [24,31].…”
Section: Sinteza Hidrogelovaunclassified
“…Ispitivanje stepena konverzije MMA pri termičkoj i polimerizaciji u mikrotalasnom polju, pokazalo je da se u opsegu temperature od 70 °C do 90 °C dostiže granična konverzija MMA od 90%, pri termičkoj polimerizaciji, dok se pri istim uslovima u mikrotalasnom polju konverzija krede od 78% do 88%, uz smanjenje snage sa 500 W na 200 W [31]. I drugi izvori pominju da se mikrotalasnom polimerizacijom metilmetakrilata i itakonata dobijaju manje molarne mase [24,31]. Poređenjem konvencionalne i mikrotalasne, izotermne sinteze hidrogelova poli(akrilne kiseline)(PAA), ustanovljeno je da se kinetike ova dva procesa, kao i dobijeni proizvodi, značajno razlikuju.…”
Section: Sinteza Hidrogelovaunclassified